Designing Of An Integrated Team Based Learning Module To Teach Undergraduate Students- Tuberculosis: Designing Of An Integrated Team Based Learning Module To Teach Undergraduate Students- Tuberculosis - Dr. Sheetal Harakuni; Dr. Reshma Davanageri; Dr. Netravati A B; Dr. Bhagyashri Patil; Dr. Jayasheela Bagi; Dr. Shilpa Bhimalli (National Journal of Integrated Research in Medicine, 2020)
Background: Medical curriculum has been revised and proposed to be competency based medical education. The curriculum proposes integrated teaching sessions. An integrated training module where in all the faculty would contribute to active learning and bring about the integration of the knowledge. The module was designed with the aim that students should illustrate the steps in clinical and laboratory diagnosis of pulmonary tuberculosis, and would demonstrate their competency by scoring more than 80% in a post test multiple choice questions based assessment. Materials & Methods: The committee of faculty from microbiology, pathology, pharmacology, respiratory medicine, anatomy, physiology was constituted to design and validate the multiple choice questions, application exercises. The faculty were trained by the expert on team based learning methodology. Team based learning was conducted on a batch of 64 students, whose perception and performance was assessed. The module was redesigned, as per studentâ€™s feedback recommendations. The module was re-administered on another set of 62 students. The perception and performance of the students was analysed. The faculty feedback was gathered. Results: An integrated module was designed wherein the students were able to illustrate the steps of clinical and laboratory diagnosis of a case of tuberculosis, with 80% accuracy. And 95% students scored â‰¥80% marks on a multiple choice question test(paired t-test=9.122 p <0.001). Faculty feedback was encouraging to implement the module. Conclusion: Integrated module can be designed on other topics adopting principles of Team based learning [Harakuni S Natl J Integr Res Med, 2020; 11(2):70-73]